Physical processes influencing the Asian climate due to black carbon emission over East Asia and South Asia - F. Luo; B. H. Samset; C. W. Stjern; M. Joshi; L. J. Wilcox; R. J. Allen; W. Hua; S. Li; S. Li (Atmospheric Chemistry and Physics, 2025)
Many studies have shown that black carbon (BC) aerosols over Asia have significant impacts on regional climate but with large diversities in the intensity, spatial distribution, and physical mechanism of regional responses. In this study, we utilized a set of systematic regional aerosol perturbations (SyRAPs) using a reduced-complexity climate model, FORTE2 (Fast Ocean Rapid Troposphere Experiment version 2), to investigate responses of the Asian climate to BC aerosols over East Asia only, South Asia only, and both regions at once and to thoroughly examine related physical processes. Results show that regional BC aerosols lead to strong surface cooling, air temperature warming in the low-level troposphere, and drying over the perturbed areas, with seasonal differences in magnitude and spatial distribution. Atmospheric energy budget analysis suggests that reductions in local precipitation primarily depend on the substantial local atmospheric heating due to shortwave absorption by BC. Increases in dry-static-energy (DSE) flux divergence partly offset the reduced precipitation over North China in summer and most of China and India in the other three seasons. Decreases in DSE flux divergence lead to a stronger reduction in precipitation over South China and central India in summer. Changes in DSE flux divergence are mainly due to vertical motions driven by diabatic heating in the middle and lower troposphere. BC perturbations also exert non-local climate impacts through the changes in DSE flux divergence. This study provides a full chain of physical processes of the local climate responses to the Asian BC increases and gives some insights to better understand the uncertainties in model responses.